Social capital for a child friendly city : housing, streets, and parks - Kinoshita, Isami; Terada, Mitsunari (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Social Capital for a Child-Friendly City argues for the importance of relationship networks (social capital) in children's growth and socialization, and explores how child-friendly social capital can be cultivated through urban planning and community development. As outdoor play decreases and children spend more time online, Kinoshita and Terada return to John Dewey's proposal that social capital is essential for nurturing the next generation and establish a democratic and sustainable society. The book features examples from Sweden, Finland, Germany, Switzerland, the UK, and Japan, exploring methods for cultivating social capital and spaces for children to play and develop in cooperative housing, outdoor play spaces, streets, parks, and neighborhoods. This book will be of use to students and practitioners of urban planning and landscape architecture, as well as any community leaders or developers seeking to foster a nurturing environment where children can flourish"--
Keywords: City children; Play environments; Social capital (Sociology); Child development; City planning; Community development; ARCHITECTURE / Urban & Land Use Planning; ARCHITECTURE / Landscape; SOCIAL SCIENCE / Sociology / Urban